Integration : CARICOM's key to prosperity : CARICOM 30th Anniversary Distinguished Lectures - Hall, Kenneth (Ian Randle KingstonJM, 2006)
Looks at the 1973 origins of the Community, describes Caribbean civilisation and explicates its unity in diversity. Deals with the place and power of culture in the region's development and looks at CARIFESTA. Discusses democratic governance in the region. Notes aspects of the region's financial market and considers the nature of contemporary globalisation . Highlights the contributions of the Caribbean diaspora to the region's development and looks at the way forwrd for the Caribbean Single market and Economy.